Easy A [videorecording (DVD)] - Gluck, Will; Stone, Emma, 1988-; Badgley, Penn, 1986-; Church, Thomas Haden; Bynes, Amanda, 1986-; Byrd, Dan, 1985- (Sony Pictures Home Entertainment, 2010)
After a little white lie about losing her virginity gets out, a clean cut high school girl sees her life paralleling Hester Prynne's in 'The Scarlet Letter, ' which she is currently studying in school. Hoping to become popular, she decides to use the rumor mill to advance her social and financial standing.